The compositional aspects of edible flowers as an emerging horticultural product - Pires Junior, Eleomar de O. (2018)
Edible flowers are becoming very popular, as consumers are seeking healthier and more attractive food products that can improve their diet aesthetics and diversify their dietary sources of micronutrients. The great variety of flowers that can be eaten is also associated with high variability in chemical composition, especially in bioactive compounds content that may significantly contribute to human health. The advanced analytical techniques allowed us to reveal the chemical composition of edible flowers and identify new compounds and effects that were not known until recently. Considering the numerous species of edible flowers, the present review aims to categorize the various species depending on their chemical composition and also to present the main groups of compounds that are usually present in the species that are most commonly used for culinary purposes. Moreover, special attention is given to those species that contain potentially toxic or poisonous compounds as their integration in human diets should be carefully considered. In conclusion, the present review provides useful information regarding the chemical composition and the main groups of chemical compounds that are present in the flowers of the most common species.